CIUDADES INTERMEDIAS EN COSTA RICA ELEMENTOS SOCIOANTROPOLÓGICOS PARA SU ESTUDIO - Castro Sánchez, Silvia (2000)
This paper presents some socio-anthropological elements to study the cultural production and the quality of life in intermedie cities of Costa Rica, in the period that goes from 1970 to 1998. The proposal begins with a general framework to analyse the relationships between development models and urbanisation processes. Next the authors discuss a concept of intermediate cities adequate to the Costa Rican situation, and present a theoretical and methodological approach useful to understand the cultural production in these cities, as well as to asses the quality of life of its inhabitants. The article concludes with a balance of opportunities and obstacles that exist to do this kind of research.